Answer:
Demetrius's account is $84 higher after the two transactions
Step-by-step explanation:
Let
x -----> original amount in Demetrius's account
y ----> amount in Demetrius's account after the deposit and the withdraws
we know that
The amount in Demetrius's account after the two transactions must be equal to the original amount in Demetrius's account plus the deposit minus the withdraws
so
![y=x+120-36](https://tex.z-dn.net/?f=y%3Dx%2B120-36)
![y=x+\$84](https://tex.z-dn.net/?f=y%3Dx%2B%5C%2484)
therefore
Demetrius's account is $84 higher after the two transactions
Answer:
6.75 hrs are missing
Step-by-step explanation:
First, change all fractions into decimals:
8 = 8
7 1/4 = 7 + 0.25 = 7.25
8 1/2 = 8 + 0.50 = 8.50
Next, add all numbers gotten together:
8 + 7.25 + 8.50 = 23.75
Subtract the number gotten from the total
30.5 - 23.75 = 6.75
~
Answer:
It will take Jade (2x + 5) minutes
Step-by-step explanation:
Let us find the expression that represents the time Jade will take
∵ Binh takes x minutes to ride to his friend’s house
∴ The time Binh takes = x minutes
∵ 5 more means + 5
∵ Twice means × 2
∵ Jade takes 5 minutes more than twice as long as Binh to ride to their
friend’s house
→ Multiply the time Binh takes by 2 and add the product by 5
∵ Binh takes x minutes
∴ The time Jade takes = 2 × x + 5
∴ The time Jade takes = 2x + 5 minutes
∴ It will take Jade (2x + 5) minutes
Answer:
D. To provide a contrast to the actual enormity of the Biltmore
Step-by-step explanation:
Usually, when something is in "quotes", it's used to indicate sarcasm, emphasis, or a direct quote. This indicated emphasis.
<span>Algebra Calculator | Latest | Discuss | About | Help | Translation</span>
20,897,614 solved | 1,346 online
Skip Ad
<span>
<span>
<span>
<span>
</span>
<span>
</span></span></span></span>
<span><span> 5x2-23x=-26</span> </span>Two solutions were found :<span><span> x = 2
</span><span> x = 13/5 = 2.600
</span></span>
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
5*x^2-23*x-(-26)=0
Step by step solution :Skip Ad
<span> Step 1 :</span><span>Equation at the end of step 1 :</span><span> (5x2 - 23x) - -26 = 0
</span><span> Step 2 :</span>Trying to factor by splitting the middle term
<span> 2.1 </span> Factoring <span> 5x2-23x+26</span>
The first term is, <span> <span>5x2</span> </span> its coefficient is <span> 5 </span>.
The middle term is, <span> -23x </span> its coefficient is <span> -23 </span>.
The last term, "the constant", is <span> +26 </span>
Step-1 : Multiply the coefficient of the first term by the constant <span> 5 • 26 = 130</span>
Step-2 : Find two factors of 130 whose sum equals the coefficient of the middle term, which is <span> -23 </span>.
<span><span>
-130
+
-1
=
-131
<span>
</span>
</span>
<span>
-65
+
-2
=
-67
<span>
</span>
</span>
<span>
-26
+
-5
=
-31
<span>
</span>
</span>
<span>
-13
+
-10
=
-23
That's it</span></span>